Systematic review of the effects of fatigue on spatiotemporal gait parameters - Barbieri, Fabio Augusto [UNESP]; Dos Santos, Paulo Cezar Rocha [UNESP]; Lirani-Silva, Ellen [UNESP]; Vitório, Rodrigo [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP]; Van Diëen, Jaap H. (SAGE Publications, 2013)
PURPOSE: This systematic review aimed to assess changes on spatiotemporal gait parameters due to fatigue. MATERIAL AND METHOD: A search was carried out in literature published from 1950 to December 2010 and retrieved 771 articles using terms referring to walking and fatigue in the title, abstract or keywords. Two researchers assessed the selection and quality of each article independently. RESULTS: Seven studies were selected for this systematic review, two of which reported on the same data set. Several spatiotemporal parameters were reported to change with fatigue, but the few variables studied in multiple studies, gait speed and stride or step length and stride time, were affected only in single studies. Fatigue appears to modulate spatiotemporal gait parameters, but the effects of fatigue appear to be dependent on the muscles that were fatigued, and age that appears to be a moderator of the effects of fatigue on gait. © 2013 - IOS Press and the authors. All rights reserved.
Keywords: Gait; motor control; muscle fatigue; spatiotemporal parameters; falling; gait; human; injury; priority journal; quality of life; review; spatiotemporal analysis; walking speed